STUDI EFEKTIVITAS PEMBELAJARAN ONLINE MELALUI APLIKASI ZOOM CLOUD MEETING TERHADAP HASIL BELAJAR SISWA - Hoeriyah, Yayah; Mansyur, Masykur H.; Sholeh, Slamet (Universitas Pakuan, 2021)
THE EFFECT OF VOCABULARY MASTERY ON ESSAY WRITING SKILLS DESCRIPTIONOnline learning is a combination of learning that continues with the seperation between teacher and learners and their learning using learnin resources through technology and communication and other media. Long-distance education is know as e-learning and as for this research, it focuses on problem that result from students learning in online learnig and aimed at learning how effective long-distance learnig can be. And the methods used library research and can be decoded online learnig through Zoom make learning effective, because of the many supporting features it provides duringteh Covid-19 pandemic.